The chronic effects of salinity on the Crustacean Moina affinis Birge (1893) (Baghdad Science Journal, 2004)
Thi s study included the effect of chronic exposure of di fferent concentrations of Nan on the biology of fresh water zroDplonk ton species Moina 41.112' ( Cladcxe'ra The concentrations used for chronic exposure were 03, 0.75. 1 960 to investigate iI effects on the life cycle and la lables of this species after exposure period and the range of this exposure effects on the rate of expectation for further life, also the effect of salinity on reproduotive parameters was studied which included average of total number of eggs and young produced, volume clutch's (6.95. indiclutch for control group , 14.516 indi clutch for 0.596a ,3_65 ind./ clutch for (175 5(.. and 03 Ind} cruel] for 1960) and number of Clutch's (5.5 clutch/ female for control group, 1.7 clutch/ funEoc for 0.5.9(z.z, 1:2 dutch?' female for 0,75960 and 0,1 oluchi female for 196.) which howed a reduction_ But had no effects on the time 10 tarsi clutch produced. Time of surviving ( 12.9 day for control g.roup. 63 day for 0.5%0, 15_2 day for 0.75%.0 and 4.6 day for I 9f,), average final length and average of daily length, growth increasing were studied_ In addition to the studying the orient of salinity on the number of moults which showed a reduction. in its number.